FRAUD DAN MONITORING DALAM PERSPEKTIF TEORI KEAGENAN - Princessa Chenkiani; Arihadi Prasetyo (Jurnal Akuntansi, 2023)
Financial fraud committed by agents at the company can have an impact on the destruction of the company which is detrimental to the owner, to control fraud in the context of the agency theory approach can be carried out with various mechanisms that can be applied to companies, to avoid intentional or unintentional mistakes. To avoid intentional errors in financial reports or fraud, in this study researchers tried to see the effect of various mechanisms implemented such as the Audit Committee, Institutional Ownership, Managerial Ownership, and Internal Control against fraud. The data analysis technique used is the quantitative method, which includes coefficient similarity tests, descriptive statistics, and logistic regression tests. The number of property and real estate companies as a sample is 38 companies with a research period of 2017-2021. The results of this study indicate that the variables Audit Committee, Institutional Ownership, Managerial Ownership, and Internal Control are not significant in reducing the tendency for fraud to occur.